Management and outcome of vein of Galen malformation. Issue 11 (6th July 2010) - McSweeney, N; Brew, S; Bhate, S; Cox, T; Roebuck, D J; Ganesan, V
Abstract : Objective: To describe our experience of treating children with vein of Galen aneurysmal malformation (VGM) in a single UK centre between 2003 and 2008. Method: Retrospective review of case notes and neuroimaging. Results: 33 children were seen (26 neonates, seven infants), of whom 28 underwent endovascular treatment. Four were not offered treatment as they had evidence of severe diffuse brain injury at presentation; treatment was deferred in another who subsequently died. Seven children died (two of whom had endovascular treatment). Of the survivors (all treated), 13 (39%) are neurodevelopmentally intact, seven (21%) have mild neurodevelopmental impairment and the remaining six (18%) have significant neurological impairment. The authors were not able to identify clinical or radiological parameters which strongly predicted outcome. Of note, two children with initially low Bicêtre scores were neurologically intact after successful embolisation. Conclusion: The outlook for children with VGM is significantly better since the advent of endovascular treatment. Decisions about the appropriateness and timing of treatment should be taken by an experienced multidisciplinary team.